The Implementation of PjBL in ICT for English Language Teaching - Firmansyah Firmansyah; Ija Try Saputri Kadir; Yetty Yetty; Sri Ayu Budi Lestari (Hasanuddin University, 2023)
The objective of this research is to investigate how the students perceive to the implementation of PjBL in ICT for English language teaching. This study applied quantitative research where questionnaire about students’ interaction, motivation, understanding, problem solving, and suitability of the subject was administered to the students. The result of this research was show that the implementation of PjBL allow the students have good interaction to other groups member. It can improve their communication and teamwork. Second, PjBL also can motivate the students to explore the subject by giving them projects so the students enthusiastic in join the class. Third, PjBL can ease them to understand the subjects given by making the projects so they can directly practice. Fourthly, their problem solving can improve because in having the projects, they must solve the problem in ICT for English language teaching. And the last is the respondents perceive that PjBL are suitable implemented in ICT for English language teaching class.